1996
DOI: 10.1111/j.1432-1033.1996.0064q.x
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Scale Chemical Synthesis and Range of Activity of Drosocin, an O‐Glycosylated Antibacterial Peptide of Drosophila

Abstract: Insects respond to a bacterial challenge by rapidly synthesizing a diverse range of antibacterial and antifungal peptides. One of them, drosocin, a 19-residue proline-rich antibacterial peptide, was isolated from Drosophila. This peptide carries a disaccharide moiety attached to a threonine residue in mid-chain position. The present report describes the enlarged-scale chemical synthesis of drosocin, glycosylated with Gal(~l+3)GalNAc(al+O). We have studied the range of activity of the synthetic glycopeptide, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
129
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 37 publications
8
129
1
Order By: Relevance
“…In contrast, no member of the penaeidin family has been extracted from shrimp in a substituted form, and O-glycosylation of recombinant penaeidins induced a two to fourfold decrease in penaeidin activity against half of the microorganisms tested [34]. In drosocin, it was proposed that the carbohydrate moiety might be involved in conformational changes beneficial to the stereospecific recognition of a target molecule on bacterial membranes [44]. However, a recent report by McManus et al on the three-dimensional (3D) structure of drosocin revealed no substantial difference in the structure of drosocin with or without the sugar part [46].…”
Section: Effect Of Posttranslational Modifications On Bioactivity Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no member of the penaeidin family has been extracted from shrimp in a substituted form, and O-glycosylation of recombinant penaeidins induced a two to fourfold decrease in penaeidin activity against half of the microorganisms tested [34]. In drosocin, it was proposed that the carbohydrate moiety might be involved in conformational changes beneficial to the stereospecific recognition of a target molecule on bacterial membranes [44]. However, a recent report by McManus et al on the three-dimensional (3D) structure of drosocin revealed no substantial difference in the structure of drosocin with or without the sugar part [46].…”
Section: Effect Of Posttranslational Modifications On Bioactivity Of mentioning
confidence: 99%
“…Similar to reports on insect cecropins [42,43], the partial loss of antibacterial activity that occurs in nonamidated penaeidins may be due to the loss of a positive charge at the COOH-terminus, and consequently to less efficient interaction of the peptide with bacterial membranes. Several antimicrobial peptides, such as the proline-rich Drosophila melanogaster drosocin [44] or the glycinerich Phormia terrano6ae diptericin [45], occur naturally as O-glycosylated molecules, and substitution is necessary for full biological activity of these peptides [1]. In contrast, no member of the penaeidin family has been extracted from shrimp in a substituted form, and O-glycosylation of recombinant penaeidins induced a two to fourfold decrease in penaeidin activity against half of the microorganisms tested [34].…”
Section: Effect Of Posttranslational Modifications On Bioactivity Of mentioning
confidence: 99%
“…After purification by RP-HPLC and control of the purity and integrity by MALDI-TOF MS, the antibacterial activity of aqueous solutions (0.1-200 M, in final concentration) of the different variants was assayed against several microorganisms. Due to the limited amounts of the synthetic glycopeptides, only three strains of the Gram-negative E. coli (D22, D31, and SBS 363), very sensitive to drosocin (27), were investigated for their susceptibility to MPAC. No growth inhibition was observed for either synthetic MPAC derivative after 24 h of culture at 30°C in Poor Broth medium at the highest concentration tested (200 M).…”
Section: Time Course Of Induction and Quantification Of Mpac-the Levementioning
confidence: 99%
“…To improve this yield of mature drosomycin (25%), we coCapillary zone electrophoresis (CZE) and matrix-assisted laser deexpressed drosomycin with the Kex2 endoprotease by insertsorption/ionisation time-of-flight mass spectrometry (MALDI-TOF-MS) were performed as described in [10].…”
Section: Cze and Maldi-tof-msmentioning
confidence: 99%